Epstein-Barr Virus and Monoclonal Gammopathy of Clinical Significance in Autologous Stem Cell Transplantation for Multiple Sclerosis. (15th January 2019) - Mehra, Varun; Rhone, Elijah; Widya, Stefani; Zuckerman, Mark; Potter, Victoria; Raj, Kavita; Kulasekararaj, Austin; McLornan, Donal; de Lavallade, Hugues; Benson-Quarm, Nana; Lim, Christina; Ware, Sarah; et al.
Abstract: Introduction: Autologous hematopoietic stem cell transplantation (AHSCT) with anti-thymocyte globulin (ATG) conditioning as treatment of active multiple sclerosis (MS) is rapidly increasing across Europe (EBMT registry data 2017). Clinically significant Epstein-Barr virus reactivation (EBV-R) following AHSCT with ATG for severe autoimmune conditions is an underrecognized complication relative to T-cell deplete transplants performed for hematological diseases. This retrospective study reports EBV-R associated significant clinical sequelae in MS patients undergoing AHSCT with rabbit ATG. Methods: Retrospective data were analyzed for 36 consecutive MS-AHSCT patients at Kings College Hospital, London. All patients routinely underwent weekly EBV DNA polymerase chain reaction monitoring and serum electrophoresis for monoclonal gammopathy (MG or M-protein). EBV-R with rising Epstein-Barr viral load, M-protein, and associated clinical sequelae were captured from clinical records. Results: All patients had evidence of rising EBV DNA-emia, including 7 who were lost to long-term follow-up, with a number of them developing high EBV viral load and associated lymphoproliferative disorder (LPD). Nearly 72% (n = 18/29) developed de novo MG, some with significant neurological consequences with high M-protein and EBV-R. Six patients required anti-CD20 therapy (rituximab) with complete resolution of EBV related symptoms. Receiver operating characteristics estimated a peak EBV viremia of >500 000 DNA copies/mL correlated with high sensitivity (85.5%) and specificity (82.5%) (area under the curve: 0.87; P = .004) in predicting EBV-R related significant clinical events. Conclusion: Symptomatic EBV reactivation increases risk of neurological sequelae and LPD in MS-AHSCT. We recommend regular monitoring for EBV and serum electrophoresis for MG in MS patients in the first 3 months post-AHSCT. Abstract : Epstein-Barr virus (EBV) reactivation is common post-transplant with anti-thymocyte globulin for multiple sclerosis, with significant lymphoproliferative and neurological sequelae associated with rising M-protein. Serial monitoring of EBV and M-protein is recommended post-transplant, as is pre-emptive anti-CD20 therapy with EBV DNA >500 000 copies/mL.